AWS storage solutions 2022 : EBS/S3/EFS/Glacier. (Pragmatic AI Solutions, 2022)
Learn to use AWS Storage Solutions Correctly. Hi, my name is Noah gift, and today I'm going to talk about AWS storage systems. We're going to talk about the elastic box system where EBS, also S3, the object storage system, which has unlimited data storage, and also EFS, the elastic file system. And finally, offsite backup, and also archiving systems with glacier, we're also going to do some demos of those products. Let's go ahead and get started. This video shoes both theory and hands on demos. * EBS (Elastic Block Storage) * EFS (Elastic File System) * S3 (Object Storage) * Glacier (Archiving) 00:00 Intro 00:49 Storage Module Overview 03:00 What is EBS? 11:00 EBS Demos 30:00 What is S3? 38:00 S3 Demos 48:00 Boto3 S3 Demos 49:00 What is EFS? 51:47 What is AWS Glacier?.